ANALISIS FAKTOR YANG MEMPENGARUHI KELENGKAPAN DOKUMENTASI EVALUASI KEPERAWATAN DI RUANG RAWAT INAP RS PERTAMINA BINTANG AMIN TAHUN 2016 - Hesti Platini; Widia Hastuti; Andoko Andoko (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2019)
Background: Hypertension or high blood pressure is still a high cause of death in the world. One factor in the occurrence of hypertension is poor nutritional status. Measurement of nutritional status is by knowing body mass index.Purpose: To describe the body mass index (BMI) values in patients with hypertension.Methods: Descriptive with cross sectional approach with consecutive sampling. The number of samples was 40 respondents. Data retrieval is measurement of blood pressure, height and weight. Data analyzed and made by frequencies and percentages.Results: The highest number of hypertension was in the age range of 60-74 years old and the highest gender in this research is women and hypertension in grade I with overweight body mass index values (35%), normal body mass index (62.5%).Conclusion: This study shows that hypertensive patients at Public Health Centre (Puskesmas Pasundan Garut) was show a high body mass index (BMI) value. By early detection to prevent of further severe complications and management of hypertension can be done to improve the quality of life.